Acute pancreatitis in pregnancy: a rare case report - Khan, Farha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Acute pancreatitis (AP) during pregnancy is a rare condition characterized by acute inflammation of pancreas due to premature activation of enzymes resulting in local pancreatic destruction and activation of an inflammatory cascade. This condition is most commonly caused by gall stones, hypertriglyceridemia, idiopathic factors. It’s very rare, incidence being 1 in 1000 to 1 in 12,000 pregnancies. Its more common in multigravida (75%) and relatively uncommon in first trimester. Patient usually present with acute severe pain abdomen radiating to back, nausea, vomiting, fever and anorexia. On examination there can be tachycardia, jaundice, epigastric tenderness, abdominal guarding and rigidity in severe cases. Serum amylase and lipase levels three times upper limit of normal value is diagnostic. Ultrasound remains imaging modality of choice. Vigorous fluid replacement is recommended. Prompt diagnosis and early treatment can prevent maternal and fetal morbidity and mortality. 23 years primigravida with 14 weeks of pregnancy came to outpatient with nausea and vomiting (10-15 episodes per day) and pain abdomen for 3 days. On abdomen examination epigastric tenderness was present. Serum amylase was 1246 Units/litre and serum lipase was 507.3 units/litre. She was given supportive care with IV fluids. Analgesics, antiemetics and antihistaminics were given. Gradually liquids were started and she recovered in 5 days.